Incidence of nontuberculous mycobacterial disease and coinfection with tuberculosis in a tuberculosis-endemic region: A population-based retrospective cohort study. Issue 52 (24th December 2020) - Lin, Chin-Kuo; Yang, Yao-Hsu; Lu, Mong-Liang; Tsai, Ying-Huang; Hsieh, Meng-Jer; Lee, Yi-Chen; Wang, Tsu-Nai; Chen, Yi-Lung; Chen, Vincent Chin-Hung
Abstract : Abstract: Nontuberculous mycobacteria (NTM) infection may interfere in the diagnosis and treatment of tuberculosis (TB) in TB-endemic regions. However, the population-based incidence of NTM disease and NTM–TB coinfection remains unclear. We used Taiwan's National Health Insurance Research Database to identify new diagnoses of NTM disease and TB from 2005 to 2013 and calculated the incidence rate and the proportion of NTM–TB coinfection. The patients with NTM disease or TB were determined by the use of disease codes from International Classification of Diseases, Ninth Revision, Clinical Modification, laboratory mycobacterium examination codes, and antimycobacterial therapy receipts. From 2005 to 2013, the age-adjusted incidence rate of NTM disease increased from 5.3 to 14.8 per 100, 000 people per year and the age-adjusted incidence rate of NTM–TB coinfection was around 1.2 to 2.2 per 100, 000 people per year. The proportion of NTM–TB coinfection among patients with confirmed TB was 2.8%. Male and older patients had a significantly higher incidence of NTM disease. The effects of urbanization and socioeconomic status (SES) on the incidences of TB and NTM disease were different. Rural living and lower SES were significantly associated with increasing the incidence of confirmed TB but not with that of NTM disease. For NTM disease, those living in the least urbanized area had significantly lower incidence rate ratio than in the highest urbanized area. The incidence of NTM–TB coinfection was higher in older patients and compared with patients aged < 45 years, the incidence rate ratio of the patients aged> 74 years was 12.5. In TB-endemic Taiwan, the incidence of NTM disease increased from 2005 to 2013. Male gender and old age were risk factors for high incidence of NTM disease. SES did not have a significant effect on the incidence of NTM disease, but rural living was associated with lower incidence of NTM disease. In TB-endemic areas, NTM–TB coinfection could disturb the diagnosis of TB and treatment, especially in elderly patients. Abstract : Supplemental Digital Content is available in the text